Performance of complexing agent in vanadium bromide redox flow battery - Heng, Ming Xuan (2015)
As the world sees the need to embrace renewable energy due to depleting fossil fuel, the market shares for better and more effective energy storage systems is expected to increase significantly. One of the promising energy storage system is the vanadium bromide redox flow cell (VBr) which uses V(II)/V(III) and Br3-/Br- couples in the negative and positive half cells respectively. However, VBr cell has a major problem associated with its cell operation. As the cell is charging, bromine gas could be liberated to endanger both the user and environment if no proper protection is in place. Escaped bromine could also reduce the efficiency of flow cell. Therefore, it is important that the bromine be captured and held within the flow cell system during cell charging to ensure safety and efficiency. Several possible bromine complexing agents were previously studied for their suitability to apply in VBr flow cell electrolyte. Among those, sample CP2 was identified to be a promising bromine complexing agent to replace the expensive N-ethyl-N-methyl-morpholinium bromide (MEM) and N-ethyl-N-methyl-pyrrolidinium bromide (MEP) currently used in the market. In this study, three flow cells were constructed to compare the performance of the CP2 infused electrolyte with a blank and MEM/MEP infused electrolyte. The flow cells were assessed based on their coulombic, voltage and energy efficiencies. Based on results obtained, CP2 is a promising alternative to MEM/MEP. CP2 infused electrolyte does not undergo phase separation during charging like MEM/MEP infused electrolyte does which could potentially reduce cost associated with cell construction. It was also observed that amount of bromine complexing agent added to the electrolyte affects the functionality of the flow cell. By upsizing the composition used in the static cell in equal proposition, it was discovered that clogging of carbon felts occurred in flow cell tests, which rendered the cell non-functional.